1990
DOI: 10.1161/01.cir.82.4.1117
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent pericarditis. Relief with colchicine.

Abstract: Recurrence is one of the major complications of pericarditis. Treatment of recurrence is often difficult, and immunosuppressive drugs or surgery may be necessary. We conducted an open-label prospective study of nine patients (seven men and two women; age, 18-64 years; mean age, 41.7 +/- 13.7 years). Patients were treated with colchicine (1 mg/day) to prevent recurrences. All patients had suffered at least three relapses despite treatment with acetylsalicylic acid, indomethacin, prednisone, or a combination. Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(47 citation statements)
references
References 24 publications
1
43
0
3
Order By: Relevance
“…Unsatisfactory results are often reported when NSAIDs are used. 20,21,55 Some of these failures are due to low dosages or courses that are too short, with interruption of the therapy while the disease is still active, as manifested by persistently elevated CRP. Articles often give no details on the specific drug.…”
Section: Nsaids and Aspirinmentioning
confidence: 99%
“…Unsatisfactory results are often reported when NSAIDs are used. 20,21,55 Some of these failures are due to low dosages or courses that are too short, with interruption of the therapy while the disease is still active, as manifested by persistently elevated CRP. Articles often give no details on the specific drug.…”
Section: Nsaids and Aspirinmentioning
confidence: 99%
“…This experience is very similar to that of Guindo and colleagues. 17 Clinical manifestations and evolution: key points c Symptoms during recurrences are similar to the index attack, the main manifestation being chest pain of pericardial characteristics c Usually clinical manifestations are more severe in the index attack, while subsequent episodes are milder. Frequently, chest pain is the only manifestation during relapses c Tamponade is infrequent during relapses, especially when not present in the index attack.…”
Section: Colchicinementioning
confidence: 99%
“…In a later prospective study, Guindo and colleagues 14 reported on 9 patients (5 idiopathic, 2 post-open heart surgery, 1 with Dressler's syndrome, and 1 with systemic lupus erythematosus) in whom NSAIDs and corticosteroids failed to prevent relapses of pericarditis (mean of 4.3 episodes per patient). All were treated with combined prednisone (20 to 60 mg/d), which was tapered and discontinued within 6 weeks, and colchicine (1 mg/d).…”
mentioning
confidence: 99%